Evaluation of pure‐component adsorption properties of silicalite based on the Langmuir and Sips models. Issue 11 (14th July 2015) - Caravella, Alessio; Zito, Pasquale F.; Brunetti, Adele; Barbieri, Giuseppe; Drioli, Enrico
<x xml:space="preserve">Abstract</x> The Langmuir and Sips models parameters were estimated for the adsorption of several light gases and hydrocarbons (H2, CH4, CO2, CO, N2, C2H6, C3H8, n‐C4H10) in silicalite along with their functionality with temperature. This is a scientific attempt to resume and reconcile the number of available experimental data and supply scientists and other operators with the adsorption properties of silicalite within a wider range of temperature and pressure. Furthermore, to provide readers with more detailed information on where each of the two models work better, the analysis is divided into three temperature ranges: low‐temperature, high‐temperature, and whole temperature range. As a result, it is found that the Langmuir model works well in the whole temperature range for the light gases considered but not for the other hydrocarbons, for which it is better to use the Sips model by splitting calculation over low‐ and high‐temperature range. © 2015 American Institute of Chemical Engineers AIChE J, 61: 3911–3922, 2015